Changes of gray matter volume and amplitude of low-frequency oscillations in amnestic MCI: An integrative multi-modal MRI study. (May 2015) - Zhao, Zhi-Lian; Fan, Feng-Mei; Lu, Jie; Li, Hui-Jie; Jia, Long-Fei; Han, Ying; Li, Kun-Cheng
Background: Numerous studies have reported that the amnestic-type mild cognitive impairment (aMCI) patients have impaired brain structural integrity and functional alterations separately. Purpose: To investigate the changes of gray matter and amplitude of low-frequency oscillations in patients with aMCI by combining structural and functional magnetic resonance imaging (fMRI). Material and Methods: Thirty-four patients with aMCI and 34 controls were recruited. We adopted optimized voxel-based morphometry to detect regions with gray matter volume (GMV) loss induced by aMCI. Then regional differences in amplitude of slow-4 band (0.027–0.073 Hz) oscillations among these regions between patients and healthy controls were examined. Both slow-4 amplitude of low-frequency fluctuations (ALFF) and slow-4 fractional ALFF (fALFF; the relative amplitude that resides in the low frequencies) were employed. Results: Patients with aMCI demonstrated significant GMV loss in the ventral medial prefrontal cortex (vMPFC), posterior cingulate cortex (PCC), bilateral hippocampus, right superior parietal gyrus, left insula and left middle temporal gyrus ( P  < 0.01). The patients exhibited significant decreases of slow-4 ALFF in the left hippocampus ( P  = 0.05) and PCC ( P  = 0.02), while the decreased slow-4 fALFF was detected in PCC ( P  = 0.01) and increased slow-4 fALFF in vMPFC ( P  = 0.03). In PCC, aMCI and controls exhibited significant different GMV-fALFF correlation ( P  < 0.05), with opposite correlation trend. Conclusion: The correlates between anatomical deficits and functional alterations in aMCI suggest that anatomical and functional deficits are linked to each other. The differences of GMV-fALFF correlations demonstrated altered anatomical-functional relationship in aMCI.